THE EFFECT OF COMMUNICATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT POS INDONESIA REGIONAL 3 BANDUNG - Dewi K Soedarsono (Sean Institute, 2023)
Communication is in everyone's interest to socialize with other people. Someone will find it difficult to connect with other people without communication between everyone. The purpose of this study was to analyze the effect of communication and work environment on employee performance at PT Pos Indonesia Regional 3 Bandung. The research method used is descriptive and verification method. Data collection was carried out using questionnaires and interviews. The sample in this study were 84 respondents. Data processing was carried out using multiple linear regression analysis, model fit test, and hypothesis testing with the T-test and data processing assisted with SPSS software tools. The findings of this study prove and provide results that communication has a positive and significant effect on employee performance, the work environment has a positive and significant effect on employee performance and communication and work environment have a positive and significant effect on employee performance.